Study of simultaneous presence of DD and PP electric fields during the geomagnetic storm of November 7–8, 2004 and resultant TEC variation over the Indian Region - Galav, P.; Sharma, Shweta; Rao, S.S.; Veenadhari, B.; Nagatsuma, T.; Pandey, R. (My University, 2014)
During very intense geomagnetic storm of November 7–8, 2004 simultaneous presence of storm time disturbance dynamo and eastward and westward directed prompt penetration electric fields inferred from the ground based magnetometer data in the 75∘ E sector is presented. Magnetometer observations show that, on the whole, average ΔH variation on 8 November remains below the night time level compared to its quiet day variation. A number of upward and downward excursions have been observed between 0130 UT and 0800 UT in the ΔH variation on 8 November. These excursions in ΔH have been attributed to the episodes of eastward and westward prompt penetrating electric fields. Ionospheric response in the equatorial ionization anomaly region along 75∘ E has also been studied using the total electron content data recorded at five GPS stations, namely Udaipur, Bengaluru (IISC), Hyderabad (HYDE), Maldives (MALD) and Diego Garcia (DGAR). Observation of markedly suppressed EIA, in conjunction with ΔH variation which was m negative during the daytime on 8 November, indicates the presence of an external field of opposite polarity (the disturbance dynamo electric field) that either undermined, or overshadowed the daytime ambient (eastward) electric field to the extent that the equatorial plasma fountain could not become effective.
Keywords: Geomagnetic storms; Electric field; Low latitude ionosphere; GPS; TEC; Indian region